2016
DOI: 10.1007/s00198-016-3718-0
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin does not play a major role in the pathogenesis of skeletal complications in type 2 diabetes mellitus

Abstract: SummaryIn contrast to previously reported elevations in serum sclerostin levels in diabetic patients, the present study shows that the impaired bone microarchitecture and cellular turnover associated with type 2 diabetes mellitus (T2DM)-like conditions in ZDF rats are not correlated with changes in serum and bone sclerostin expression.IntroductionT2DM is associated with impaired skeletal structure and a higher prevalence of bone fractures. Sclerostin, a negative regulator of bone formation, is elevated in seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Although the aim of this study was to find a possible association between levels of sclerostin and periodontal disease, other variables were also investigated, but no significant correlations with sclerostin were found, which is in agreement with data described by Pereira et al. (2016) . Thus, it is not possible to affirm that sclerostin contributed to periodontal disease in either the diabetic or nondiabetic populations.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although the aim of this study was to find a possible association between levels of sclerostin and periodontal disease, other variables were also investigated, but no significant correlations with sclerostin were found, which is in agreement with data described by Pereira et al. (2016) . Thus, it is not possible to affirm that sclerostin contributed to periodontal disease in either the diabetic or nondiabetic populations.…”
Section: Discussionsupporting
confidence: 85%
“…Studying the role of sclerostin in the pathogenesis of DM2 in rats, Pereira et al. (2016) concluded that DM2 has a harmful effect on the microarchitecture of cancellous and cortical bone due to the reduction in bone formation and increase in resorption. However, the data indicate that the changes in bone microarchitecture and turnover associated with DM2 in rats are not a consequence of sclerostin expression.…”
Section: Discussionmentioning
confidence: 99%
“…A recent abstract suggests that there is no or little relationship between serum sclerostin and skeletal sclerostin in mice (Baldock- ASBMR abstract, 2016). Similarly, a recent study in diabetic rats suggested the sclerostin does not have a major role in skeletal alterations of T2D [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Although an in vitro study reported an increased production of sclerostin by osteocyte-like cell line when cultured in hyperglycaemia (Tanaka et al 2015b, Pereira et al 2016), our recent study shows that the impaired bone microarchitecture and cellular turnover associated with T2DM-like conditions in diabetic ZDF rats are not correlated with changes in serum sclerostin levels, bone sclerostin expression or osteocyte viability (Pereira et al 2017). On the other hand, high fat diet in mice resulted in increased serum sclerostin and dramatic alterations of osteocyte network organisation (Mabilleau et al 2016).…”
Section: Sclerostinmentioning
confidence: 53%
“…Despite increased osteoblastogenesis, no direct effect of GLP-1RAs on bone nodule mineralisation in vitro was shown with up to 100 nM of exenatide and 1000 nM of liraglutide (Ma et al 2013, Pereira et al 2015. It is well established that exposure of primary osteoblast cells to high glucose levels inhibits in vitro bone nodule formation (Balint et al 2001, Pereira et al 2017. Interestingly, despite no effect of exenatide on bone formation in normal glucose conditions, unpublished results from our group demonstrate that it can reduce the deleterious effect of glucose on bone formation in vitro, in a dose-dependent manner.…”
Section: In Vitro Studiesmentioning
confidence: 99%